Bile Acids Elevated in Chronic Periaortitis Could Activate Farnesoid-X-Receptor to Suppress IL-6 Production by Macrophages - Cao, Shan; Meng, Xinyu; Li, Yixuan; Sun, Li; Jiang, Lindi; Xuan, Hanqing; Chen, Xiaoxiang (Frontiers in Immunology, 2021)
Chronic periaortitis (CP) is a rare autoimmune disease without effective treatment. By analyzing the serum bile acid spectrum in 28 CP patients with the ultra-performance liquid chromatography-tandem mass spectrometry, we found that the bile acids were significantly altered in CP patients, with significant increases in chenodeoxycholic acid (CDCA) and glycochenodeoxycholic acid (GCDCA) and decrease in deoxycholic acid (DCA). Signalling pathway enrichment analysis from the RNA sequencing results suggested that the altered gene sets in PBMC of CP patients were associated with bile acid metabolism. Furthermore, we found that pathological concentration of CDCA could significantly inhibited IL-6 expression in RAW 264.7 cells after LPS stimulation. Since CDCA is a well-known natural high-affinity ligand for the bile acid receptor farnesoid-x-receptor (FXR) while GW4064 is the synthetic specific agonist of this receptor, we then revealed that GW4064 significantly decreased IL-6 expression in RAW 264.7 cells and bone marrow-derived macrophages but not in FXR-/- macrophages upon LPS stimulation. The western blot results with the anti-FXR antibody showed significantly increased expression in the nuclear proportion, suggesting that FXR agonist promoted the transportation of FXR into the nucleus but did not increase the FXR expression in macrophages. Dual-luciferase report assay and ChIP assay demonstrated that upon activation, FXR could directly bind to the promoter site of IL-6, leading to the decreased expression of IL-6. Thus, bile acids, especially CDCA, may operate to damp inflammation via FXR-mediated downregulation of IL-6 in mononuclear cells and provide a protective mechanism for CP patients.